2019
DOI: 10.1186/s12995-019-0237-x
|View full text |Cite
|
Sign up to set email alerts
|

Desired improvements of working conditions among medical assistants in Germany: a cross-sectional study

Abstract: Background In outpatient care in Germany, medical assistants (MAs) are the contact persons for patients’ concerns and their working conditions are relevant to their own health and the provided quality of care. MAs working conditions have been described as precarious leading to high levels of work stress. Consequently, we aimed to examine MAs’ needs for work-related improvements. Methods We surveyed 887 employed MAs between September 2016 and April 2017. A 20-item questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(35 citation statements)
references
References 55 publications
0
33
0
2
Order By: Relevance
“…As a previous study of our group has shown, the prevalence of work-related intervention needs is high among MAs [22]. Furthermore, there was no evidence of associations between the unmet work-related intervention needs and various individual or practice related factors.…”
Section: Discussionmentioning
confidence: 59%
See 4 more Smart Citations
“…As a previous study of our group has shown, the prevalence of work-related intervention needs is high among MAs [22]. Furthermore, there was no evidence of associations between the unmet work-related intervention needs and various individual or practice related factors.…”
Section: Discussionmentioning
confidence: 59%
“…This suggests that there are no specific subgroups that need to be taken into account when planning interventions. Instead, all MAs should be targeted [22].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations